Overview of ocean power technology. (15th May 2019) - Wilberforce, Tabbi; El Hassan, Zaki; Durrant, A.; Thompson, J.; Soudan, Bassel; Olabi, A.G.
Abstract: This work discusses and provides a critical expose of some of the newly emerging renewable energy technologies with special concentration on marine energy generation. The work shows that there are several promising new developments in harvesting marine energy and it examines some of these technologies and discusses their advantages and some of the obstacles that are impeding the commercialization of these emerging technologies. This includes wave energy harvesting, tidal energy harvesting, ocean thermal energy and the utilisation of salinity gradients for electricity generation. The work emphasises the fact that these new emerging technologies are currently at the developing stages and has a long way to go before successful commercialization and wide adoption become the norm. The work stresses the need for more research and developmental work to address several of the technical issues that need to be addressed including devices designs, their installation and maintenance, the infrastructure which includes the grid and power transmission as well as losses, their use in arrays, and their longevity. This work underlines the lack of reliable studies on the long term impacts of these technologies on both the marine environment and nearby habitations and highlights the need for proper environmental and social impact assessments of these technologies. The work concludes that combination of technical, policy and economic advances will enable marine energy technologies to play a large role in combination with currently adopted non-pollution renewable energy resources to provide the world population with their energy needs and contribute to affecting significant reduction in the use of non-renewable and other polluting fuels worldwide.